5-Bromo-1H-indole-3-carbaldehyde thiosemicarbazone - Rizal, Mohd Razali; Ali, Hapipah Mohd; Ng, Seik Weng (International Union of Crystallography, 2008)
In the essentially planar title molecule, C10H9BrN4S, the C=N double bond is in a trans configuration. In the crystal structure, the S atom acts as a hydrogen-bond acceptor for the aromatic NH, aliphatic NH and terminal NH2 groups of three symmetry-related molecules, forming a weak hydrogen-bonded layer structure.